2005
DOI: 10.1161/01.cir.0000150335.01285.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Progression of Incidental, Asymptomatic Lesions Discovered During Culprit Vessel Coronary Intervention

Abstract: Background-With the reduction in restenosis rates by drug-eluting stents, there is new controversy concerning the optimal management of incidental, nontarget lesions identified during percutaneous coronary intervention (PCI). Such lesions have been treated conservatively because of risk of restenosis but now are being considered for PCI to prevent plaque instability. However, the impact of incidental stenoses on future cardiac events remains unknown. Methods and Results-We performed a retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
142
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(161 citation statements)
references
References 43 publications
12
142
2
5
Order By: Relevance
“…The PROSPECT study16 of coronary atherosclerosis demonstrated that cardiac events were related to high atherosclerotic burden rather than the severity of coronary artery stenosis. It is now accepted that atherosclerotic burden in coronary arteries is more important than stenosis in predicting subsequent cardiovascular events17, 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…The PROSPECT study16 of coronary atherosclerosis demonstrated that cardiac events were related to high atherosclerotic burden rather than the severity of coronary artery stenosis. It is now accepted that atherosclerotic burden in coronary arteries is more important than stenosis in predicting subsequent cardiovascular events17, 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…Natural history studies have revealed that most coronary events were preceded by rapid plaque expansion that was unusual and unrelated to baseline plaque burden [22][23][24]. IPH, with the capability to induce changes in plaque behavior [25], may play a critical role in the pathogenesis of coronary events.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] More recent studies have demonstrated that plaques progress from mild at baseline to obstructive at the time of MI and clarified that plaque progression occurs before actual plaque rupture. 16,[31][32][33] In addition, as described later, angiography often substantially underestimates plaque severity, as revealed by intravascular ultrasound imaging, contributing to the misconception of the mild vulnerable plaque.…”
Section: Circulation Research June 19 2015mentioning
confidence: 95%
“…In the Dynamic Registry of the National Heart, Lung, and Blood Institute, 31 3747 patients undergoing percutaneous coronary intervention were retrospectively studied. In this cohort, 216 patients required an additional percutaneous coronary intervention of a nonculprit lesion within 1 year.…”
Section: Circulation Research June 19 2015mentioning
confidence: 99%